(untitled) (REGE Revista de Gestão, 2018)
AbstractPurpose – The purpose of this paper is to investigate the extent to which the organizational commitment andjob satisfaction influence intent to turnover. Design/methodology/approach – Following a quantitative approach regarding methodological aspects ofthis research, a case study was carried out in a company of information technology and communication locatedin Porto Digital, in the Northeast of Brazil. A data collection technique with 172 forms, a self-administered formwith 18 closed questions with a Likert-type scale and an open questionnaire were used. In this analysis,Statistical Package for the Social Sciences (SPSS) software was used as the technique; besides the descriptivestatistics, a correlation was made between dependent variables (intention of rotation) and independent variables(affective, normative, instrumental and work satisfaction). The level of organizational commitment in its threedimensions (affective, normative and instrumental), the job satisfaction in its five dimensions (satisfaction withnature of the task, with leadership, with colleagues, with salary and promotions) and the level of intent toturnover from the respondents were investigated. Findings – The results suggest that affective and normative commitments and satisfaction with pay,satisfaction with promotions and satisfaction with the nature of the work are correlated with the intention ofnegative turnover significantly. Among the demographic factors, only the age showed a negative correlationwith intent to turnover. By performing multiple regression analysis, we identified that the variables that mostimpacted the turnover intention are affective commitment, satisfaction with salary and normativecommitment. The qualitative portion of this study was accomplished through a content analysis of the openquestion of the form. Finally, one of the main considerations is the findings that revealed variables other thanthose adopted in the study, which influence the permanence of the respondents. Research limitations/implications – Among the limitations of the research a single case studyis highlighted that replicates the experience in other ICT companies to verify if the results foundare similar in other organizations and in other segments. The findings direct the construction andvalidation of new scales, the creation of qualitative protocols to identify the variables that influencethe retention of a specific group of individuals to serve as a guide for the elaboration of a questionnaire,as well as creation of surveys of longitudinal nature to correlate the data of intention of rotation with theeffective turnover. Practical implications – Based on the results, organizations can reduce voluntary evasion by adjustingactions, policies and practices, directing those responsible for People Management to attract andretain good employees. It should be emphasized that voluntary turnover should be treated as one of themanagement indicators of greater relevance by organizations, representing a thermometer of all humancapital management. Social implications – The monitoring of employment and unemployment levels is part of the public policyagenda for generating employment and income in Brazil. For organizations, employee turnover can andshould be managed and monitored so that appropriate levels are found and their consequences are minimizedthrough effective solutions. The results are important both for technology-based organizations and for allstakeholders interested in the subject as the public power. Originality/value – Although in the international literature turnover is a topic of study for many years, in theBrazilian context, there is a shortage of research on the subject, specifically in the sector of advanced technologywhere there is a great lack of skilled labor, a fierce competition and where to keep employees standard highbecomes a survival factor. This study may contribute to the exploration in the local literature, as it will helplocate the academy on the Brazilian reality and open the doors to new research works on turnover and itspossible correlations with other variables besides organizational commitment and job satisfaction. Keywords Organizational commitment, Turnover, Job satisfaction